(untitled) - Filak, Vincent F (Los Angeles, 2016)
Content of the book dynamics of Media Writing gives students transferable skills that can be applied across all media platforms-from traditional mass media formats like news, public relations, and advertising to emerging digital media platforms. Whether issuing a press release or tweeting about a new app, today's media writers need to adapt their message for each specific media format in order to successfully connect with their audience
Keywords: Phương tiện truyền thông đại chúng,Nghề làm báo,Mass media,Journalism; Tác Quyền,Sổ tay, sách hướng dẫn, vv,Authorship